Sabbath controversy in Matthew - Viljoen, Francois P. (Verbum et ecclesia, 2011)
Jesus’ attitude towards the Sabbath plays a crucial part in Matthew’s argument. Some scholars argue that Jesus provocatively broke the Sabbath law; however, an attentive reading of the Sabbath controversies revealed a different reality. Matthew strategically places the Sabbath stories after he has firmly stated Jesus’ teaching on the continuing validity of the law and the requirement of greater righteousness. The law and the prophets are fulfilled in the Person of Jesus, who demonstrated a fresh approach to Sabbath observance. God’s intention with the Sabbath must also be recognised. Matthew argues not if the Sabbath should be observed, but how it should be done to experience true rest according to the will of God.